Causas e consequências do descompasso das pequenas e médias empresas nacionais do setor de autopeças: 1975 a 1990 - Oujeiko, George (1993)
This work is intended to locate the small and midsize components makers within the industrial contex in Brazil, as well as, to point out the importance of its role in Auto parts.Sector. The picture of domestic auto market and external, the relationship with vehicle's assemblers and the other auto-parta companies -large national and foreigners with minors- on brazilian economy, was realised. The change occurred in global market for rise of niponic carmakers in world scenary, such as challenged the 'ocidental' auto industries status, with their new industrial paradigms, that wich made significant transformations in auto-parts branch. The choosen period 1975 to 1990, i8 justified, because represent the three phases, that determined the main events brasilian expansion, recession and stagnation of domestic cal' market. The cal' global war and consequence on vehicle improvements in the BO'ties, brought to brasilian market deep change. This events caused several factors, that converging on small and midsized auto-parts, that affected particulary the minors firmas -unsettle their performanced. The impact of new industrial and administrations tecnics, on traditional manufactoring families companies management, was made and, the analysis at the role of such enterprises and their .perspective on 90'decade, too. The other topics herein approached, being made analysis on role of State and it relation with vehicle and auto-parts makers; the independent auto-parts commercial system; maintenance and consumers and emergent of marginal components in brasilian spare parts market.